The predictive embodied mind: a case-based encounter with film aesthetics - Coëgnarts, Maarten (Frontiers in Neuroscience, 2025)
In recent decades, the scientific study of the mind has experienced two significant conceptual shifts, each reshaping its research focus. The first, embodied cognition, questioned the objectivist framework of first-generation cognitive science by emphasizing that mental processes are deeply grounded in sensorimotor interactions with the world. Image-schemas have been suggested as one of the foundational conceptual elements underpinning this embodied grounding. The second shift is the revival of perception as an inferential process within the Predictive Processing (PP) framework. PP conceptualizes the mind as a predictive machine that minimizes error by actively anticipating sensory input through probabilistic computations. Rooted in Helmholtz’s theory of unconscious inference and updated as the Bayesian brain model, PP has been extended to diverse cognitive phenomena, including perception, emotion, and aesthetics. While its application to the visual arts and cinema has been relatively limited, this article seeks to advance this encounter by bridging PP with cinematic aesthetics. The article is structured into three sections. The first introduces the PP framework, outlining its core theoretical principles and linking it to the concept of image schemas. The second section reviews existing accounts of predictive processing in visual aesthetics, particularly in the non-temporal arts, and introduces a new case study of narrative painting that builds on Ladislav Kesner’s work on PP in art interpretation. In the final section we move to the temporal art form of narrative cinema, proposing that films engage the brain’s inferential processes by activating image schemas through deliberate formal design. By structuring sensory input in alignment with the brain’s predictive logic, cinematic works of art enhance both comprehension and the aesthetic pleasure derived from resolving predictions into coherent patterns.